Recapitulation of thymic function by tissue engineering strategies - Silva, Catarina S. (2021)
The thymus is responsible for the development and selection of T lymphocytes, which in turn also participate in the maturation of thymic epithelial cells. These events occur through the close interactions between hematopoietic stem cells and developing thymocytes with the thymic stromal cells within an intricate 3D network. The complex thymic microenvironment and function, and the current therapies to induce thymic regeneration or to overcome the lack of a functional thymus are herein reviewed. The recapitulation of the thymic function using tissue engineering strategies has been explored as a way to control the bodyâ s tolerance to external grafts and to generate ex vivo T cells for transplantation. In this review, the main advances in the thymus tissue engineering field are disclosed, including both scaffold- and cell-based strategies. In light of the current gaps and limitations of the developed systems, the design of novel biomaterials for this purpose with unique features is also discussed.